2019
DOI: 10.1101/725986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variations in the coverage of biological soil crusts along a gradient of aridity in the center-west of argentina

Abstract: 18The biological soil crusts (biocrust) play a fundamental role in the arid and semiarid areas of 19 South America. However, little attention has been paid to the distribution and coverage of them. In 20 Argentina, studies about biocrust are still scarce. The goal of this contribution is to analyze the 21 coverage of the biocrust and each of the functional component along a gradient of aridity in the center-22 west of Argentina. The gradient included three differentiated sites: semiarid, arid, and hyperarid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In relation to the characteristics of the environments where biocrusts are found, our data compilation shows occurrences from extremely dry to highly humid environments (Castillo-Monroy et al 2016 , Navas Romero et al 2019 , Hakkoum et al 2020 , Samolov et al 2020 ). However, information on environmental characteristics and species occurrence seems to be limited, since there are more studies in arid and semiarid climate, and almost all genera were reported for these regions (Román et al 2018 , Williams et al 2018 , Roncero-Ramos et al 2019 , Szyja et al 2019 , Romero et al 2020, Zhao et al 2021 ).…”
Section: Discussionmentioning
confidence: 81%
“…In relation to the characteristics of the environments where biocrusts are found, our data compilation shows occurrences from extremely dry to highly humid environments (Castillo-Monroy et al 2016 , Navas Romero et al 2019 , Hakkoum et al 2020 , Samolov et al 2020 ). However, information on environmental characteristics and species occurrence seems to be limited, since there are more studies in arid and semiarid climate, and almost all genera were reported for these regions (Román et al 2018 , Williams et al 2018 , Roncero-Ramos et al 2019 , Szyja et al 2019 , Romero et al 2020, Zhao et al 2021 ).…”
Section: Discussionmentioning
confidence: 81%